2013
DOI: 10.1088/0268-1242/28/3/035005
|View full text |Cite
|
Sign up to set email alerts
|

Fast growth with crystal splitting of morphology-controllable Bi2S3 flowers on TiO2 nanotube arrays

Abstract: Bi 2 S 3 crystals with flower-like morphologies are deposited on TiO 2 nanotube arrays (NTs) by applying the cathodic pulse electrodeposition (PED) technique at 120 • C in 20 s. The highly oriented TiO 2 NTs/Ti serving as substrate has high surface energy which is favorable for Gibbs free energy decreasing in nucleation process. Numerous boundaries between NTs are nucleation sites for atomic clusters, resulting in a fast nucleation velocity. Effective and fast heterogeneous nucleation initiates a thermodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…On the other hand, similar to the reported Co 3 O 4 nanowire assembly behaviour, 19,24,25 its 1D nanowire precursor can easily grow into sheaf-like bundles according to the crystal-splitting mechanism. [20][21][22][23] In our experiments, the urea acts not only as a reactant in regulating the growth of the nanowire precursor, but also as a surfactant in aligning the growth of the nanowires along one direction and inducing them to gather as a ring in the centre and fan out (Fig. 3b-d).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…On the other hand, similar to the reported Co 3 O 4 nanowire assembly behaviour, 19,24,25 its 1D nanowire precursor can easily grow into sheaf-like bundles according to the crystal-splitting mechanism. [20][21][22][23] In our experiments, the urea acts not only as a reactant in regulating the growth of the nanowire precursor, but also as a surfactant in aligning the growth of the nanowires along one direction and inducing them to gather as a ring in the centre and fan out (Fig. 3b-d).…”
mentioning
confidence: 81%
“…3c), whose orientations gradually deviate from those of the initial crystal, indicating that these microspheres may be formed by the splitting crystal growth mechanism. 14,[20][21][22][23] Finally, these assemblies transformed into uniform pompon-like Co 3 O 4 aer a continuous hydrothermal reaction for longer than 6 h (Fig. 3d).…”
mentioning
confidence: 97%
“…Bi 2 S 3 is an attractive material because of its narrow bandgap ( E g  = 1.3 eV) and high photo-to-electron conversion efficiency [28]. The Bi 2 S 3 /TiO 2 heterostructure can reduce the recombination of photogenerated electrons and holes, and this effect would benefit the photoelectric performance of materials [2932]. However, no research has been reported on the photogenerated cathodic protection property of Bi 2 S 3 /TiO 2 nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, numerous ordered superstructures including dendritic structures, 8,9 hierarchical microspheres, 10 flower-like 11 and nanorodassembled hollow superstructures, 12 etc. have been fabricated, and diverse methods such as the electrochemical method, 13,14 the CVD technique, 15 and the solution approach [16][17][18][19] have been introduced to control these morphologies.…”
Section: Introductionmentioning
confidence: 99%